Metrological evaluation of the performance of a grid-connected system in a tropical climate according to IEC 61724-1;2021 and ISO/IEC guide 98-3:2008 (GUM) (Research, Society and Development, 2026)
This study establishes a technical benchmark for photovoltaic (PV) generation estimates in low-latitude tropical climates. To this end, a comprehensive metrological evaluation was conducted on a 4.41 kWp grid-connected PV system, monitored from June 2013 to May 2014 in strict compliance with IEC 61724-1:2021 and the ISO/IEC Guide 98-3 (GUM). This normative framework ensures metrological traceability and statistical consistency across the analyzed quantities. The Performance Ratio (PR), Capacity Factor (CF), and Final Yield (Yf) serve as synthetic indicators of the system's optical, thermal, and electrical losses. Literature seldom incorporates measurement uncertainties into these metrics, which constrains international comparisons and diminishes inferential reliability. This study applies a full uncertainty treatment, enhancing the statistical robustness of performance estimates. Results indicate an annual Performance Ratio of 0.864 ± 0.054 (k = 2; 95% confidence level), with variations ranging from 0.789 to 0.940. The average Capacity Factor reached 19.2%, while the Final Yield achieved 4.61 kWh/kWp·day—values exceeding typical ranges reported for equivalent systems in tropical regions. The findings demonstrate high solar resource exploitation and confirm the technical viability of PV technology at low latitudes. This study consolidates a solid metrological foundation for inter-system comparisons and for the validation of performance models in tropical environments.